2015
DOI: 10.1080/10871209.2015.1020579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Recreationists’ Awareness and Attitudes Toward Piping Plovers (Charadrius melodus) at Lake McConaughy, Nebraska, USA

Abstract: Piping plovers (Charadrius melodus) are shorebirds federally protected by the U.S. Endangered Species Act that often nest on beaches in proximity to human recreation. We evaluated whether awareness of piping plovers and their legally protected status and attitudes toward species management varied between groups of recreationists at Lake Mc-Conaughy, Keith County, Nebraska, USA. Awareness of piping plovers varied primarily by the respondents' number of annual visits to Lake McConaughy; the respondents' age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our overall approach was similar to Jorgensen & Brown (2015), but here we build upon the earlier study by developing questions that identify impacts that influence visitors' acceptance of Piping Plovers. We surveyed visitors by conducting personal interviews on beaches at Lake McConaughy from 18 May to 21 Jul 2015 during the Piping Plover breeding season.…”
Section: Interview Questions and Field Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our overall approach was similar to Jorgensen & Brown (2015), but here we build upon the earlier study by developing questions that identify impacts that influence visitors' acceptance of Piping Plovers. We surveyed visitors by conducting personal interviews on beaches at Lake McConaughy from 18 May to 21 Jul 2015 during the Piping Plover breeding season.…”
Section: Interview Questions and Field Methodsmentioning
confidence: 99%
“…We used (1) primary recreation activities (fishing, boating, camping, swimming and socializing), (2) accompanied by a dog, (3) number of annual visits during the nesting season, and (4) the visitors' sex, age and awareness of the presence of Piping Plovers at Lake McConaughy as variables in a set of a priori models. We included sex and age of the visitor in our models because previous research (Jorgensen & Brown 2015) showed those variables were associated, albeit weakly, with attitudes toward Piping Plovers; that same study showed location of principal residence was not associated with attitudes towards Piping Plovers. We included awareness (yes or no) of Piping Plovers at Lake McConaughy in our models because awareness of a protected species in a beach setting has been associated with negative attitudes toward that species (Maguire et al 2013).…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The period overlaps with the Piping Plover breeding season, which extends from mid-April through July Wilson 2013, 2014). The majority of recreationists visiting the lake are from the Front Range Urban Corridor (FRUC; Cheyenne, Wyoming to Denver and Colorado Springs, Colorado) or from the local area (Jorgensen and Brown 2015). The majority of plovers nest along the north shore of Lake McConaughy because extensive sand beaches are present only on this side of the lake.…”
Section: Study Areamentioning
confidence: 99%
“…In practice, the size and configuration of exclusion zones are left to the discretion of local managers whose experience with the species and best management practices may be lacking. Consequently, the buffer distances of exclusion zones are highly variable, with reported distances ranging from 16 to 800 m (USFWS 1994, 2003, Jorgensen and Brown 2015.…”
Section: Introductionmentioning
confidence: 99%